Efek Antihiperkolesterolemia Ekstrak Etanol Herba Alfafa (Medicago sativa) Pada Tikus Putih Jantan - Ika Puspitaningrum; Lia Kusmita; Wahyuning Setyani (Fakultas Farmasi Universitas Setia Budi, 2016)
Hypercholesterolemia is a disorder characterized by an increased concentration of cholesterol in the blood. Alfalfa (Medicago sativa) is one of the plants that are believed to control blood cholesterol. This study aims to determine antihypercholesterolemia effect of herb alfafa ethanol extract and the effective dose. Test antihypercholesterolemia ethanol extract of herb alfalfa using male Wistar rats as many as 30 individuals were divided into 6 groups. Group 1 (normal control) was given standard feed. Group 2 (negative control) was given CMC Na 0,5%. Group 3 (positive control) was given Simvastatin. Groups 4, 5 and 6 was given herb alfafa ethanol extract 270, 540 and 1080 mg/kg rat. All treatments are given 7 days orally. Induction hypercholesterolemia with high-fat feed a mixture of standard rat food with lard and egg yolk duck (3:1), as well as fructose 1.8 g/kg rat. Induction was given to all groups for 50 days, except for the normal control. Measurement of total blood cholesterol levels was done on days 0, 51 and 58. Cholesterol levels were obtained calculated % decline further tested with SPSS statistical release 16. The test results showed a statistically significant difference between the negative control group with the ethanol extract of herb Alfalfa three doses. While the comparison between the positive control with the ethanol extract of the herb alfalfa three doses showed no significant differences. It was provided that the ethanol extract of the herb alfalfa could affected antihypercholesterolemia, but not comparable to Simvastatin. The effective dose of ethanol extract of alfalfa as antihypercholesterolemia was 270 mg/kg rat.